Effect of Somatostatin Analogue (SMS 201-995) Administration on Portal Blood Flow in Patients with Liver Cirrhosis - S. KAPICIOĞLU; O. YEŞİLDAĞ; E. OVALI; A.H. BAKİ; N. KAYA (Turkish Journal of Gastroenterology, 2020)
-